MUC5B rs35705950 and its association with survival in Brazilian patients with idiopathic pulmonary fibrosis: A longitudinal cohort study - Rogerio Rufino; Luana Faria; Marcelo Ribeiro-Alves; Lucas Resende Martinez Araujo; Leonardo Palermo; Elizabeth Bessa; Bruno Rangel; Mariana Carneiro Lopes; Mariana Costa Rufino; Cláudia Henrique da Costa; Jeane de Souza Nogueira; Cíntia Barros Santos-Rebouças; et al. (PLoS ONE, 2026)
Background Idiopathic pulmonary fibrosis (IPF) is a progressive interstitial lung disease with heterogeneous clinical outcomes. The MUC5B promoter polymorphism (rs35705950) is the most consistent genetic factor associated with IPF susceptibility, but data from Latin American populations remain limited. Methods We conducted a longitudinal cohort study including 50 patients with IPF and 45 healthy controls, recruited between August 1, 2018, and April 30, 2025, at a tertiary referral center in Brazil. Genotyping of rs35705950 was performed by real-time PCR. Demographic, clinical, and functional data were collected at baseline. Survival was analyzed using Kaplan–Meier curves and Cox regression models, with follow-up defined from symptom onset to death or censoring. Results The T-allele frequency was higher in IPF patients compared with controls (47.1% vs 8.3%, p < 0.001). Carriers of the T allele (G/T or T/T) comprised 82.4% of cases versus 16.7% of controls. Among patients with IPF, T-carriers tended to have worse lung function and shorter survival, although survival differences were not statistically significant. In multivariable models, the presence of the T allele was not an independent predictor of mortality. By contrast, higher New York Heart Association (NYHA) functional class was consistently associated with increased mortality risk. Conclusions In this Brazilian cohort, the MUC5B promoter variant was strongly associated with susceptibility to IPF but not with independent survival differences. Functional impairment, particularly NYHA class, remained the key prognostic factor. These findings highlight the importance of integrating genetic and clinical information in diverse populations and provide novel data from an underrepresented Latin American setting.